2002
DOI: 10.1007/s00213-002-1110-6
|View full text |Cite
|
Sign up to set email alerts
|

Actions of α-2 noradrenergic agonists on spatial working memory and blood pressure in rhesus monkeys appear to be mediated by the same receptor subtype

Abstract: The identical pattern of dose-dependent reversal of cognitive improvement and hypotension indicates that, in non-human primates, the same receptor subtype mediates both effects. Previous evidence suggests that the most likely candidate is the alpha-2A receptor subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Indeed, the same knockdown of DISC1 in rat PFC used in the present study has now been shown to lower the threshold for stress-induced working memory deficits (19), consistent with the altered PFC physiology observed in the current study. Moreover, our results showing that reducing cAMP with guanfacine rescues pyramidal cell function in DISC1 compromised neurons are consistent with numerous reports showing that guanfacine improves working memory in rats (60, 62) monkeys (41, 60, 6366) and humans (67–70) through inhibition of cAMP signaling in the PFC (41, 60). Taken together, these findings provide a plausible mechanism for working memory deficits observed in mice and humans in which DISC1 is impaired (2, 71).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the same knockdown of DISC1 in rat PFC used in the present study has now been shown to lower the threshold for stress-induced working memory deficits (19), consistent with the altered PFC physiology observed in the current study. Moreover, our results showing that reducing cAMP with guanfacine rescues pyramidal cell function in DISC1 compromised neurons are consistent with numerous reports showing that guanfacine improves working memory in rats (60, 62) monkeys (41, 60, 6366) and humans (67–70) through inhibition of cAMP signaling in the PFC (41, 60). Taken together, these findings provide a plausible mechanism for working memory deficits observed in mice and humans in which DISC1 is impaired (2, 71).…”
Section: Discussionsupporting
confidence: 92%
“…This almost unique versatility of clonidine in the clinical arena is somewhat surprising in view of its known sedative properties; and its antihypertensive action would be considered an off-target side effect for many of the compound's noncardiovascular indications. Even more surprising is that despite initial sedation associated with clonidine administration, the drug has been reported to produce cognition enhancement in animal models, most particularly nonhuman primates (see Terry et al 1993;Franowicz and Arnsten 2002). The less-sedating α 2 -adrenergic agonist guanfacine also shares this clonidine-like action in monkeys (Arnsten et al 1988;Avery et al 2000).…”
Section: Introductionmentioning
confidence: 93%
“…Second, clonidine has consistently shown greater side effects compared with both guanfacine and lofexidine in terms of orthostatic hypotension, sexual dysfunction and withdrawal syndrome following cessation, (Gish, Miller, Honey, & Johnson, 2010; Sorkin & Heel, 1986). In addition, guanfacine has been shown to enhance selective executive and inhibitory control processes underlying impulsivity and other behavioral factors associated with outcome in substance abuse (Brady, Gray, & Tolliver, 2011; Sofuoglu, DeVito, Waters, & Carroll, 2013) in non-human primates (Franowicz & Arnsten, 2002), healthy volunteers (Jakala, Riekkinen, Sirvio, Koivisto, Kejonen, et al, 1999; Jakala, Riekkinen, Sirvio, Koivisto, & Riekkinen, 1999) and other clinical populations (Swartz, McDonald, Patel, & Torgersen, 2008). Conversely, although few studies assessing the cognitive profile of lofexidine have been conducted, one study documented decreased cognitive efficiency after lofexidine administration compared with placebo, in fourteen opioid dependent individuals stabilized on methadone (Schroeder et al, 2007).…”
Section: Guanfacine As a Medication For Substance Abuse Compared Withmentioning
confidence: 99%